Decarbonising ceramic manufacturing: A techno-economic analysis of energy efficient sintering technologies in the functional materials sector. Issue 16 (December 2019) - Ibn-Mohammed, T.; Randall, C.A.; Mustapha, K.B.; Guo, J.; Walker, J.; Berbano, S.; Koh, S.C.L.; Wang, D.; Sinclair, D.C.; Reaney, I.M.
Abstract: The rising cost of energy and concerns about the environmental impact of manufacturing processes have necessitated the need for more efficient and sustainable manufacturing. The ceramic industry is an energy intensive industrial sector and consequently the potential to improve energy efficiency is huge, particularly through the introduction of modern sintering technologies. Although several energy efficient sintering processes have been developed, there is no comprehensive techno-economic analysis which compares and contrasts these techniques. This paper presents a critical review and analysis of a number of sintering techniques and compares them with the recently developed cold sintering process (CSP), including mode of operation, sintering mechanism, typical heating rates, duration of sintering, energy consumption profile and energy saving potential, limitations, key challenges for further development and current research efforts. By using a figure of merit, pounds per tonne of CO2 saved (£/tCO2 -eq), which links initial capital investment with energy savings, within a framework derived from ranking principles such as marginal abatement cost curves and Pareto optimisation, we have demonstrated that under the scenarios considered for 3 separate functional oxides ZnO, PZT and BaTiO3, CSP is the most economically attractive sintering option, indicating lower capital costs and best return on investment as well as considerable energy and emission savings. Although the current work establishes the viability of CSP as a competitive and sustainable alternative to other sintering techniques, the transition from laboratory to industry of CSP will require hugely different facilities and instrumentation as well as relevant property/performance validation to realise its full potential.